The impact of various calcium sources offered to Arabic hens during their early-laying stage on calcium consumption and egg production (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The research was conducted to calculate feed, calcium (Ca) intake, Ca requirements, and egg production for Arabic hens during the early egg-laying period. Materials and Methods: A total of 135 30-week-old Silver female Arabic pullets were randomly allocated to one of three treatments with five replicate cages with a semi-scavenging system of nine pullets per cage in a completely randomized design and allowed to choose Ca from limestone and oyster shells. As a control (T1), pullets were only given a complete feed with Ca and phosphorus percentages according to Hy-line International in 2018. Other treatment feeds were control feed without limestone fed with a combination of limestone (T2) or oyster shell (T3) separately. Results: The treatments had no effect (p > 0.05) on feed, grit and Ca intake (gm/bird/week), egg weight (gm), egg mass, egg production (%), and feed efficiency, but had an effect (p < 0.05) on Ca concentration (%). Ca concentration was the same at T1 and T3, and both were higher than at T2. Conclusion: The female Arabic chickens could fulfill Ca requirements by selecting from different sources of Ca. Limestone is better than the oyster shell as a source of Ca. The Ca requirement for Arabic hensin the early laying period based on the Ca concentration of the feed intake is sufficient at around 3.64% since producing the same number of egg production and heavier egg weight compared to a higher Ca level.J. Adv. Vet. Anim. Res., 10(1): 30–41, March 2023http://doi.org/10.5455/javar.2023.j649